Midfacial tumours: a review of 72 cases - A. M. Bridgeman,* M. J. Murphy,* A. Sizeland, D. Wiesenfeld (Blackwell Synergy, 2000)
Neoplastic disease of the midface (other than cutaneous lesions) is relatively uncommon and includes a disparate group of lesions. The midface is anatomically complex, consisting of several intercommunicating anatomical spaces, some of which are deeply positioned, allowing tumours to grow to an appreciable size and remain asymptomatic until late in their course.